Alveolar ridge preservation with a collagen cone: Histological, histochemical, and immunohistochemical results of a randomized controlled clinical trial - Sigmar Schnutenhaus; Cornelia Edelmann; Jens Dreyhaupt; Heike Rudolph; Ralph G. Luthardt; Werner Goetz (Wiley, 2020)
Abstract Objectives The objective of the present study was to examine the influence of a combination material of a collagen cone and a collagen membrane on the healing process of extraction sockets with regard to histological, histochemical, and immunohistochemical parameters. Materials and methods In a prospective randomized clinical study, 10 patients (test group) received a collagen combination material after tooth removal. The extraction sockets of 10 other patients (control group) were left to heal without further intervention. Eleven ±1 weeks after tooth extraction, histological biopsies were performed in both groups at the time of implant placement. Subsequently, the biopsies were evaluated semiquantitatively in terms of histological, histochemical, and immunohistochemical parameters for the identification of factors of bone metabolism and vascularization. Results No significant difference between test and control group were found for any parameter. According to the descriptive data, the use of a collagen combination material seems to result in slightly higher values of the osteogenic Runt‐related transcription factor 2 (Runx2) and vascularization. Conclusion The histological, histochemical, and immunohistochemical analysis of ARP with a collagen cone combined with a collagen membrane showed no significant differences in terms of bone metabolism and vascularization.